Penentuan Prioritas Perawatan Berdasarkan Hasil Track Quality Index (TQI) Jalur Kereta Api Antara Stasiun Semarang Poncol – Stasiun Alastua: Determining Maintenance Priority Based On The Results Of The Track Quality Index (TQI) Of Railways Between Semarang Poncol Station – Alastua Station - Rusman Prihatanto; Bima Aji Bani Nurfaizin; Armyta Puspitasari; Wawan Riyanta (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
PT. Kereta Api Indonesia (Persero) has a measuring train that is used to determine the condition of the railroad tracks. The output of measuring train is a railroad quality value called the TQI (Track Quality Index). The TQI value can used to determine priority rail road maintenance. This study aims to determine the TQI category of the railroad between Semarang Poncol - Alastua, then determine improvement priorities and maintenance programs. The results of the analysis of the Semarang Poncol-Alastua cross-section railway data have an average category II for 20 < TQI ≤ 35. For priority treatment based on the results of the first point TQI on the SMT-ATA upstream track KM 0+156/188 Type Device LK (arch) with a TQI value of 48.1 categories III with an alert condition, an immediate corrective action program and track laying. Downstream track ATA-SMT KM 1+993/975 with a TQI value of 48.1 categories III with an alert condition, an immediate corrective action program and for the type of repair is track laying.